Does a Specific Sequential Combination of Antiseptic Solutions for Chemical Debridement in Periprosthetic Joint Infection Improve Outcomes vs. Solution Alone? An In Vivo Study - Miguel Márquez-Gómez; Marta Díaz-Navarro; Andrés Visedo; Lourdes Prats-Peinado; Patricia Muñoz; Javier Vaquero; María Guembe; Pablo Sanz-Ruíz (Antibiotics)
Background: Chemical debridement is a fundamental step during the surgical treatment of both acute and chronic periprosthetic joint infection (PJI). However, there is no consensus on the optimal solution, nor is there sufficient evidence on the optimal irrigation time and combination of solutions. In an in vitro study, our group recently demonstrated that sequential combination debridement (SCD) with 3% acetic acid (AA) followed by 10% povidone iodine (PI) and 5 mM hydrogen peroxide (H2O2) was the best strategy for reducing bacterial load. The present study aimed to validate these findings in an in vivo model. Results: The median (IQR) log CFU/mL was lower in the group of mice treated with SCD (2.85 [0.00–3.72]) than in the Bactisure™ group (4.02 [3.41–4.72], p = 0.02). While this reduction was also greater than in the PI group (3.99 [1.11–4.33]), the difference did not reach statistical significance (p = 0.19). Cell viability assays showed no differences between treatments. S. aureus bacteremia was detected in 10% of mice treated with SCD, compared to 30% in the PI group and 10% in the Bactisure™ group. The difference was not statistically significant (p = 0.36). Conclusion: Our findings confirm that SCD significantly reduced bacterial load in an in vivo S. aureus PJI model, showing superior anti-biofilm activity compared to Bactisure™ and comparable performance to PI alone. These results highlight SCD’s potential to serve as a standardized chemical debridement protocol, combining enhanced efficacy with clinical applicability. Methods: We tested SCD with 3% AA for 3 min, 10% PI for 3 min, and H2O2 for 3 min in a 7-day Staphylococcus aureus (ATCC29213)-based murine femur PJI model and compared the results with single treatments of 10% PI for 3 min or Bactisure™ solution for 3 min. A sterile steel implant with local administration of saline solution for 3 min was used as a non-infected control. After completing irrigation procedures, under anesthesia, mice were euthanized, and implants were analyzed for CFU/mL counts and cell viability rates. Blood cultures were obtained pre-euthanasia to detect bacteremia.